Sequential Transformation of Zirconium(IV)‐MOFs into Heterobimetallic MOFs Bearing Magnetic Anisotropic Cobalt(II) Centers. (27th August 2018) - Yuan, Shuai; Qin, Jun‐Sheng; Su, Jian; Li, Bao; Li, Jialuo; Chen, Wenmiao; Drake, Hannah F.; Zhang, Peng; Yuan, Daqiang; Zuo, Jinglin; Zhou, Hong‐Cai
Abstract: Heterometallic metal–organic frameworks (MOFs) allow the precise placement of various metals at atomic precision within a porous framework. This new level of control by MOFs promises fascinating advances in basic science and application. However, the rational design and synthesis of heterometallic MOFs remains a challenge due to the complexity of the heterometallic systems. Herein, we show that bimetallic MOFs with MX2 (INA)4 moieties (INA=isonicotinate; M=Co 2+ or Fe 2+ ; X=OH −, Cl −, Br −, I −, NCS −, or NCSe − ) can be generated by the sequential modification of a Zr‐based MOF. This multi‐step modification not only replaced the linear organic linker with a square planar MX2 (INA)4 unit, but also altered the symmetry, unit cell, and topology of the parent structure. Single‐crystal to single‐crystal transformation is realized so that snapshots for transition process were captured by successive single‐crystal X‐ray diffraction. Furthermore, the installation of Co(NCS)2 (INA)4 endows field‐induced slow magnetic relaxation property to the diamagnetic Zr‐MOF.